A practical review of shorter than excitation wavelength light emission processes. Issue 4 (20th April 2020) - Moffatt, J. E.; Tsiminis, G.; Klantsataya, E.; de Prinse, T. J.; Ottaway, D.; Spooner, N. A.
Abstract: Shorter-than-excitation-wavelength (STEW) optical emissions, where photons originating in a material have higher energies than those that created them, have in the past few decades become important in science and medicine, with applications ranging from improving the efficiency of solar cells to creating new lasers and performing background-free microscopy of biological samples. Assigning and predicting the origin of STEW emissions is critical for accelerating development and applications of new processes and materials. In this review, we examine the different processes underlying STEW emissions and outline pathways to identify them using readily available experimental techniques.